2017
DOI: 10.31539/leea.v1i1.25
|View full text |Cite
|
Sign up to set email alerts
|

Teachers Perceptions about the Importance of English for Young Learners

Abstract: The problem of the research was, What are teachers perceptions about the importance of English for Young Learners at Elementary Schools in Lubuklinggau Timur I?. The objective of the research was to find out teachers perceptions about the importance of English for young learners at Elementary Schools in Lubuklinggau Timur I . The sample of the research was 83 teachers from 4 Elementary Schools in Lubuklinggau Timur I. The samples were taken through cluster random sampling. The researcher used survey research a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 3 publications
0
15
0
4
Order By: Relevance
“…The result of the study showed that EFL teacher trainers prefer language education to start at the first stage of primary school and even earlier during preschool. Supriyanti (2012) as cited in Oktaviani & Fauzan (2017) through her study showed the reasons of the importance English to be learned since early age, such as in the relation with the widespread assumption that the children are better than adults in learning a new language, the fact that economic globalization demands English in the form of workforce who speak English, and the parents' enthusiasm to provide their children with English learning in order to have social and economic benefits.…”
Section: Nomentioning
confidence: 99%
“…The result of the study showed that EFL teacher trainers prefer language education to start at the first stage of primary school and even earlier during preschool. Supriyanti (2012) as cited in Oktaviani & Fauzan (2017) through her study showed the reasons of the importance English to be learned since early age, such as in the relation with the widespread assumption that the children are better than adults in learning a new language, the fact that economic globalization demands English in the form of workforce who speak English, and the parents' enthusiasm to provide their children with English learning in order to have social and economic benefits.…”
Section: Nomentioning
confidence: 99%
“…These researchers only focus on age as a major factor. Some of the results of these studies come from Butler (2019), Wang & Dostal (2017), Oktaviani & Fauzan (2017), Wati (2016), and Khairani (2016. It is screening the results of their research in the following graph.…”
Section:  Introductionmentioning
confidence: 99%
“…The term 'young learner' indicates in a sizeable chronological age span, from around three years of age until 15 (Wang & Dostál, 2017). Based on their age and grade, young learners categorized in three groups, the first is very young learners around in 3-6 years old is called pre-school education, the second is young learners, they are 7-9 years old, and the third is older or late young learners, they are 10-12 years old (Oktaviani & Fauzan, 2017) Learning the language at primary ages has begun by many countries at the primary level (Oktaviani & Fauzan, 2017). The language, in this case, English, will be more easily learned because the children are in the golden age learner.…”
Section:  Introductionmentioning
confidence: 99%
“…Kemampuan berbahasa Inggris sangat dibutuhkan bila seseorang ingin memiliki kehidupan yang maju (Nishanthi, 2018). Ditambah lagi dengan kenyataan bahwa usia terbaik untuk mempelajari suatu bahasa dimulai dari usia anak-anak, karena usia anak-anak mempunyai kemampuan lebih mudah dalam mengingat, memahami dan mempelajari suatu bahasa, terutama pada periode emas anak, sehingga pembelajaran bahasa Inggris menjadi lebih efektif dilakukan (Oktaviani & Fauzan, 2017).…”
unclassified